IMPLEMENTASI MODEL FLIPPED CLASSROOM TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK : STUDY LITERATUR REVIEW - Febriasari, Ayu; Siburian, Jodion; Sadikin, ali (Universitas Muhammadiyah Pontianak, 2025)
Teachers must be able to implement a curriculum that supports students in this digital era. Through the use of creative models in the classroom, educators can guide students' critical thinking abilities. A learning approach known as the “flipped classroom” combines online and face-to-face teaching. Before face-to-face teaching, online learning was thought to help students become more independent and develop their critical thinking skills. The flipped classroom became famous during the new normal era of the Covid-19 pandemic. The flipped classroom is here as a solution so that the learning carried out can still stimulate students' thinking abilities. There are several other innovative models that can be integrated with the flipped classroom, including problem based learning, project based learning, and discover learning models. Several researchers have also innovated by developing flipped classroom-based learning tools, all of which have had a positive effect in improving students' critical thinking abilities. This research examines literature from a number of journals that use the flipped classroom concept to help students develop their critical thinking skills. Based on the research results, students' thinking abilities can be improved by using the flipped class model in the classroom, either combined with project or problem-based learning, or by creating special tools for the flipped class.